PENERAPAN PROGRAM PENANGGULANGAN STUNTING: PEMBERIAN EDUKASI DAN TABLET TAMBAH DARAH (TTD) UNTUK MENCEGAH ANEMIA PADA REMAJA PUTRI - Ni Kadek Yuni Lestari; Desak Made Ari Dwi Jayanti; Ni Luh Putu Thrisna Dewi; Ni Made Nopita Wati; Nyoman Sudarma (Politeknik Negeri Sriwijaya, 2023)
Stunting is one of the indicators of chronic malnutrition that occurs due to deficiency of nutrient intake or infectious diseases that occur in a long period of time. Iron affects the hemoglobin levels of adolescents who are growing and the increased need for iron caused by the menstrual process. Giving Blood Add Tablets to prospective brides, pregnant women and young women is a joint effort between the government and the community to prevent stunting. This community service activity was carried out through four stages, namely socialization of activities to teachers and students, distributing questionnaires before and after the activity to measure the level of knowledge and attitudes of students, providing health education and finally giving blood tablets and involving teachers as program evaluators. The results of community service activities were 28 people (78%), female respondents aged 16 years (78%), female sex as many as 36 people (100%), the level of knowledge before being given counseling the majority were in the less category as many as 24 people (67%) and after being given counseling some Majority in the good category as many as 17 people (47%), adolescent attitudes in preventing anemia before being given counseling were mostly in the less category as many as 18 people (50%) and after being given counseling mostly in the good category as many as 24 people (67%). It is suggested to the school to form a monitoring team for taking medication from the peer group as an effort to monitor students in taking medication regularly. Keywords: Stunting, education, anemia